Social Responsibility and Environmental Policy: Complementarities and Challenges - Pulgar Vidal, Manuel (2010)
Traditionally, environmental regulation has focused on compliance with environmental management standards. Consequently, a neglect of its raison d'être has been generated: the protection of the fundamental right to a healthy environment. This has created the difficulty of assembling the protection of human rights with social responsibility policies and strategies. Based on this proposed line, the author emphasizes citizen participation in which, through access to information, the process and justice, allows the integration of the community. For this reason, the design of an environmental policy framework with elements of sustainable development that the author proposes is justified. In this way, to refer to an environmental policy in Peru, the following schemes are proposed: first, depending on the regulatory framework, environmental regulations must evolve to become practical and thus lead to adequately articulated social responsibility strategies that generate mechanisms demandable. Second, the author highlights the challenge of sustainability in which the different systematic actions integrate economic, social and environmental variables. Given this, there will be a fundamental role in combining SR through effective institutionality. Third, it is necessary to create a mechanism that ensures citizen participation. In conclusion, it is important to focus on SR as an inclusive practice through citizen action, generating a policy of integration and inclusion that Peru demands.